Faktor Yang Berhubungan Dengan Obesitas Remaja Putri Di Jakarta Timur - Wilis, Sekar Woro; Ilmi, Ibnu Malkan Bakhrul; Octaria, Yessi Crosita (Media Gizi Kesmas, 2025)
Background: According to Basic Health Research (RISKESDAS) 2018, obesity prevalence in Jakarta is higher among women. In adolescent girls, obesity can persist into adulthood, causing reproductive issues. The factors contributing to obesity include energy and fat intake, body image perception, and physical activity. Objectives: This study analyzes the relationship between energy intake, fat intake, physical activity, and body image with obesity. Methods: This study is quantitative research with a cross-sectional design. The research was conducted at SMAN 98 Jakarta and SMAN 105 Jakarta, involving 108 female students aged 15-18 years from April to May 2024. Data were collected using stratified random sampling and analyzed using Spearman Rank for non-normally distributed variables and Pearson for normally distributed variables. Obesity variables were measured using BMI for age (BMI/A) and Bioelectrical Impedance Analysis; energy and fat intake were assessed using a 24-hour food recall instrument; body image was measured using the Multidimensional Body-Self Relations Questionnaire Appearance Scales. Results: The correlation between energy and fat intake with obesity showed coefficients of r=0.035 (p=0.722) and r=0.074 (p=0.448) for body fat percentage, and r=-0.016 (p=0.869) and r=-0.034 (p=0.726) for BAZ. Physical activity correlated with obesity at r=0.197 (p=0.041) for body fat percentage and r=0.156 (p=0.107) for BAZ. Body image correlated with obesity at r=0.291 (p=0.002) for body fat percentage and r=0.309 (p=0.001) for BAZ. Conclusion: The variables significantly associated with the occurrence of obesity are physical activity (when measured using body fat percentage) and body image. Meanwhile, the variables not associated with the occurrence of obesity are physical activity when measured by Body Mass Index for age (BMI for age), energy intake, and fat intake.